APLIKASI ISC (INFORMATICS STUDENT CENTER) MENGGUNAKAN METODE PERSONAL EXTREME PROGRAMMING BERBASIS ANDROID - Rizka Anjuliani; Lastri Widya Astuti; Hartini Hartini (UNIVERSITAS INDO GLOBAL MANDIRI)
Gathering for informations today can be classified as a primary need. Various kinds of activities can be done using technology, especially smartphones, for example, learning, interacting with other people, searching for information, or just for entertainment. There are many kinds of activities and many variety to access them. So it cannot be done all at once in a practical way, we need a solution to be able to carry out these activities at once with easy access. The above issue is one of the problems which is faced by the University of Indo Global Mandiri (UIGM). In order for learning and getting information can be done at once and easily accessible, then the researcher do research that aims to build applications Informatics Student Center (ISC) which is developed by using the Personal Extreme Programming (PXP) consisting of several phases, such as requirements, planning, iteration initialization, design, implementation, and system testing. ISC applications using the Android operating system, built with the collaboration of the Java language, PHP, and MySQL database. In addition to ease of access, the ISC has some features that academic information, discussion forums, entertainment, and job opportunity. Based on test results, it was concluded that the ISC application can run on Android mobile devices which are tested. Result from this study is the availability of applications supporting learning activities and access information that can be accessed online through the Android mobile devices